Socialization of Making Fermented Forages for Animal Feed in Nagari Sariak Laweh - Dwi Yuzaria; Nuraini Nuraini; Muhammad Sehir; Lusi Azzahra (Warta Pengabdian Andalas, 2024)
Sariak Laweh is a Nagari in the Indonesian province of West Sumatra's Akabiluru sub-district, Limapuluh Kota Regency. Farmers and breeders of livestock provide the majority of people's livelihoods. Nagari Sariak Laweh has much potential for planting crops like rice and vegetables. In addition, farmers and breeders in Sariak Laweh report a need for more livestock feed. This program aims to educate farmers about fermented forage animal feed and provide them with the necessary skills. Farmers can autonomously create and produce animal feed, which can reduce the amount of input and associated costs. The community engagement service was delivered through lecture and discussion techniques, which included direct conversations, practice sessions, and presentations by subject-matter experts. In order to manufacture fermented forage animal feed, farmers receive training from students. Therefore, this training would help breeders become more adept at using fermented forage animal feed in the field. The products from the training were prepared rice straw and processed corn waste that are ready for fermentation so that farmers can use them as feed samples in the future.